Deserción, permanencia y graduación, una discusión preliminar: el caso del Recinto de Golfito de La Universidad de Costa Rica. - Lezcano Calderón, Yendry (2018)
This article seeks to present the first findings of a research project which is intended to discover thefactors that have influenced the students who enrolled in the campus between the years 2006 and 2015 todrop out, to be delayed in their studies or to graduate. To accomplish this goal, the researchers did aliterature review based on theories and other investigations about the subject matter, which resulted in theconstruction of two questionnaires for the active and inactive participants of the study since the universityapplications do not necessarily show the required information in an accurate and easy way.